Biomechanical Finite Element Analysis of Bone Tissues with Different Scales in the Bone Regeneration Area after Scoliosis Surgery - Yang, Xiaozheng; Fu, Rongchang; Li, Pengju; Wang, Kun; Chen, Huiran; Fu (Journal of medical and biological engineering, 2024)
Purpose This paper aims to analyze the influence of mechanical force on bone regeneration from macro and micro perspectives, to investigate the mechanical response of bone tissues at various scales after operation and provide a theoretical basis for further research and clinical practice. Methods An effective postoperative lumbar model was constructed, and the bone regeneration area was established at the osteotomy. The area was divided into five stages, from 10 MPa to 100 MPa. Then, the osteon and bone lacuna-osteocyte models were constructed, and their biomechanical characteristics under different working conditions were studied. Results From the first stage to the fifth stage, the macroscopic bone tissue larger than 3000 µε decreased by about 40%, the maximum stress ratio n approximates k (E O /E T ) of macro- and micro-bone tissues, and the area of osteocytes less than 3000 µε increased by about 45%. In the second stage, 41.7% of the bone cells have a strain of 1000 µε ∼ 3000 µε, and this percentage increases to 66.7%∼72.2% after the fourth stage. Conclusion The macro-meso stress ratio is related to the tissue strength around the osteon. In the first stage, the patient should lie flat and rest, instead of standing upright. At the beginning of the fourth stage, the rate of bone regeneration is much faster than the rate of lesions, making it suitable for upright recovery, and the recovery speed increases.